Revaluing optical techniques in the light of vortex- and ultrasound-assisted microextraction - Gomez, Natalia Andrea (2025)
The main objective of this review is to provide an overview of the coupling between microextraction techniques (mainly based on the use of vortex and ultrasound) and different optical techniques in order to demonstrate that their combination can be a valid and accessible option for the determination of chemical species at trace or ultra-trace level. This revaluation of conventional optical techniques, including detection by digital imaging, is related to the concept of democratic analytical chemistry, and refers to the possibility of generating quality results even in laboratories with limited resources and little access to sophisticated instrumentation. In addition, the development of greener solvents and new adsorbent materials expand the capacity and versatility of the microextraction techniques, making them more effective and environmentally friendly options. In summary, the article aims to draw the attention of researchers to techniques that usually fall into disuse but, in combination with appropriate preconcentration procedures, can be attractive and economical choices for routine analysis of organic and inorganic species.